Evaluating the Effectiveness of ADR Mechanisms in Cambodia: Implications for Justice Education and Policy - Phyny Sin; Sarom Mok; Mengheang Hor; Sovantha Ros (Universitas Majalengka, 2026)
This study investigated how well alternative dispute resolution (ADR) methods work in Cambodia, and how they relate to education about justice and the creation of policies. Data were collected from 300 respondents (ADR practitioners, conflict resolution practitioners, parties to disputes and the general public) using a structured questionnaire. Descriptive statistics, Pearson correlation and multiple regression analysis were conducted in SPSS based on the data. As a result of these findings, we have found that ADR mechanisms are highly effective in resolving disputes and improving procedures. Mediation was perceived to be effective (M = 4.15, S.D. = 0.60) among respondents and thus, it is a positive sign that ADR mechanisms are effective. The correlations show that mediation (r = .68, p < .01), reconciliation (r = .66, p < .01) and negotiation (r = .65, p < .01) are very positive for ADR mechanisms. Several regression analyses showed that ADR mechanisms significantly predict the overall effectiveness. The regression model was statistically significant (R² = .52, p < .01) with mediation being the most significant predictor. These results also confirmed the effectiveness of ADR systems with mediation. And, ADR is an effective driver for lower court workload, judicial efficiency and social harmony, in addition to the results. ADR systems also advance justice education through the development of legal awareness and professional and institutional capacities. These findings are in line with the requirement of ADR to be integrated into the system of law education and policy-building.